The Repeatable Battery for the Assessment of Neuropsychological Status for Hearing Impaired Individuals (RBANS-H) before and after Cochlear Implantation: A Protocol for a Prospective, Longitudinal Cohort Study - Claes, Annes J.; Mertens, Griet; Gilles, Annick; Hofkens-Van den Brandt, Anouk; Fransen, Erik; Van Rompaey, Vincent; Van de Heyning, Paul (Frontiers in Neuroscience, 2016)
Background: Currently, an independent relationship between hearing loss and cognitive decline in older adults is suggested by large prospective studies. In general, cochlear implants improve hearing and the quality of life in severely to profoundly hearing impaired older persons. However, little is known about the effects of cochlear implantation on the cognitive evolution in this population. Aim of the study: The primary goal of this prospective, longitudinal cohort study is to explore the cognitive profile of severely to profoundly postlingually hearing impaired subjects before and after cochlear implantation. In addition, the current study aims to investigate the relationship between the cognitive function, audiometric performances, quality of life and self-reliance in these patients. Methods: Twenty-five patients aged 55 or older, scheduled for cochlear implantation, will be enrolled in the study. They will be examined prior to implantation, at six and twelve months after implantation and annually thereafter. The test battery consists of (1) a cognitive examination, using the Repeatable Battery for the Assessment of Neuropsychological Status adapted for Hearing impaired persons (RBANS-H), (2) an audiological examination, including unaided and aided pure tone audiometry, speech audiometry in quiet and speech audiometry in noise, (3) the administration of three questionnaires evaluating quality of life and subjective hearing benefit and (4) a semi-structured interview about the self-reliance of the participant. Discussion: Up until now only one study has been conducted on this topic, focusing on the short-term effects of cochlear implantation on cognition in older adults. The present study is the first study to apply a comprehensive neuropsychological assessment adapted for severely to profoundly hearing impaired subjects in order to investigate the cognitive capabilities before and after cochlear implantation. Trial registration: The present protocol is retrospectively registered at Clinical Trials (ClinicalTrials.gov) on June 9th, 2016. The first participant was enrolled on June 22nd, 2015. The protocol identifier is NCT02794350.